PERANCANGAN VIRTUAL PRIVATE NETWORK DENGAN SERVER LINUX PADA PT. DHARMA GUNA SAKTI - Trihadi, Siswa; Budianto, Frenky; Arifin, Wirriyanto (CommIT (Communication and Information Technology) Journal, 2008)
Purpose of this research is to analyze and design a network between head and branch office, andcompany mobile user, which can be used to increase performance and effectiveness of company in doingtheir business process. There were 3 main methods used in this research, which were: library study, analysis,and design method. Library study method was done by searching theoretical sources, knowledge, and otherinformation from books, articles in library, and internet pages. Analysis method was done by doing anobservation on company network, and an interview to acquire description of current business process andidentify problems which can be solved by using a network technology. Meanwhile, the design method wasdone by making a topology network diagram, and determining elements needed to design a VPN technology,then suggesting a configuration system, and testing to know whether the suggested system could run well ornot. The result is that network between the head and branch office, and the mobile user can be connectedsuccessfully using a VPN technology. In conclusion, with the connected network between the head andbranch office can create a centralization of company database, and a suggested VPN network has run well byencapsulating data packages had been sent.Keywords: network, Virtual Private Network (VPN), library study, analysis, design